الأسرة نواة وجود وأمل منشود قراءة تربوية اجتماعية للمقاصد الأُسرية - Helal, Majdy (Journal of Contemporary Maqasid Studies, 2024)
The Muslim family in Islamic and non-Muslim societies faces different challenges that hinder its existence, function, and future. At the top of these challenges is the lack of maqasid-based comprehension of the family and its relation to all aspects of life and the impact it had on the function, role, relationships, transactions, and even on its position in these societies and their future. The legal situation, contemporary family education, and the climates of upbringing in Arab and non-Arab societies and the personalities it produces with differing attitudes, inclinations, values, and aspirations lack the clarity of the essence of the family’s purposes and the relationship of these purposes to their lives. This article clarifies these maqasid and their relationship to the educational social, and psychological aspects of the family and it also illustrates the roles and functions of the family in educational and social sciences and their relationship to the Islamic purposes of the Muslim family and its future and activation.